Penyimpanan Mesocarp Tanaman Kelapa Sawit Hasil Persilangan dan Kaitannya dengan Kualitas Minyak Kelapa Sawit - Nina Unzila Angkat (Prodi. Agroteknologi dan Perkebunan, Universitas Tjut Nyak Dhien, 2023)
Introduction: This study aims to determine the effect of mesocarp storage period on the quality of free fatty acids in refined palm oil. Research Method: This study was carried out in December 2019-February 2020 at the Aek Loba Asahan Gardens, North Sumatra. The data collection used in this study is Exploration Research Method and the samples selected were genetic material from crosses that produced 15 oil palm families thought to be capable of producing low free fatty acid palm oil. Research Results: There are 15 families of oil palm that show changes in free fatty acid levels with different patterns. Three families of oil palm FL 1181, FL043 and FL133 have a long shelf life with free fatty acid levels which tend to be low for 16 days after harvest.